2015
DOI: 10.4238/2015.june.29.13
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in drought-tolerant sugarcane roots

Abstract: ABSTRACT. Drought is one of the most frequent abiotic stresses limiting the productivity and geographical distribution of sugarcane culture. The use of drought-tolerant genotypes is one approach for overcoming the effects of water stress. We conducted a comparative study to identify gene expression profiles under water stress in tolerant sugarcane roots. Two different cultivars, 1 drought tolerant (RB867515) and 1 drought susceptible (SP86-155), were evaluated at 4 sampling time points (1, 3, 5, and 10 days) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
1
15
0
2
Order By: Relevance
“…However, the association between genotype and phenotype remains a challenge, despite many attempts 36,37 . Several studies have identified drought-induced genes in order to identify targets for molecular breeding 25,[38][39][40] . However, as most of these studies only harvest at one timepoint, it is possible that important rhythmic drought-induced genes are missed 41 .…”
Section: Rhythms In Field Conditions Are Different From Those In Contmentioning
confidence: 99%
“…However, the association between genotype and phenotype remains a challenge, despite many attempts 36,37 . Several studies have identified drought-induced genes in order to identify targets for molecular breeding 25,[38][39][40] . However, as most of these studies only harvest at one timepoint, it is possible that important rhythmic drought-induced genes are missed 41 .…”
Section: Rhythms In Field Conditions Are Different From Those In Contmentioning
confidence: 99%
“…Vantini et al (2015) observed differentially expressed genes between tolerant and sensitive sugarcane varieties along time (1, 3, 5, and 10 days after withholding water) in root tissues. At the beginning of the stress (1 and 3 days), genes encoding proteins with protection function (chaperones, heat shock proteins, antioxidant enzymes and protease inhibitor proteins) were induced in the tolerant variety.…”
Section: Differential Gene Expression Under Drought Stressmentioning
confidence: 99%
“…Little is known about the bHLH family in plants. Vantini et al (2015), investigating the effects of water deficit in sugarcane, observed the expression of bHLH after 3 days of water stress (complete absence of irrigation). Studying A. thaliana, Hao et al (2012) concluded that bHLH, together with factors that interact with phytochromes, regulates cell elongation and plant development in response to light and hormones.…”
Section: Genes Induced In the Sensitive Cultivarmentioning
confidence: 99%
“…However, most transcriptome studies (e.g., microarrays, SAGE, cDNA-AFLP) in sugarcane (Rodrigues et al, 2009;Kido et al, 2012;Vantini et al, 2015), as well as the study of Vargas et al (2014) using the RNA-Seq technology, have evaluated the effect of short-term water stress (usually the complete absence of irrigation) and of water stress in young plants. These designs can lead to poorly acceptable results regarding the drought sensitivity or tolerance of plants under real field conditions where water restriction usually lasts for several months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation